2010
DOI: 10.1161/circulationaha.109.863795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Dyssynchrony After Myocardial Infarction in Patients With Left Ventricular Dysfunction, Heart Failure, or Both

Abstract: Background-Mechanical dyssynchrony is considered an independent predictor for adverse cardiovascular outcomes in patients with heart failure. However, its importance as a risk factor after myocardial infarction is not well defined. Methods and Results-We examined the influence of mechanical dyssynchrony on outcome in patients with left ventricular dysfunction, heart failure, or both after myocardial infarction who were enrolled in the Valsartan in Acute Myocardial Infarction (VALIANT) echocardiography study. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 44 publications
4
71
0
3
Order By: Relevance
“…Advanced MRI techniques and speckle-tracking strain-related imaging (with 3-dimensional reconstruction) with ultrasound echocardiography have been shown to improve early predictions of outcomes in humans. 212 These new approaches may more accurately measure ventricular volumes and diastolic function in both small-and large-animal models. 213 If MRI is not available, then 3-dimensional transdiaphragmatic echocardiography or 2-dimensional transdiaphragmatic echocardiography should be considered (to alleviate problems with finding useable echocardiography windows).…”
Section: Noninvasive Imaging Modalitiesmentioning
confidence: 99%
“…Advanced MRI techniques and speckle-tracking strain-related imaging (with 3-dimensional reconstruction) with ultrasound echocardiography have been shown to improve early predictions of outcomes in humans. 212 These new approaches may more accurately measure ventricular volumes and diastolic function in both small-and large-animal models. 213 If MRI is not available, then 3-dimensional transdiaphragmatic echocardiography or 2-dimensional transdiaphragmatic echocardiography should be considered (to alleviate problems with finding useable echocardiography windows).…”
Section: Noninvasive Imaging Modalitiesmentioning
confidence: 99%
“…39 The ability of strain imaging to quantify the regional timing of deformation has led to its widespread application in the assessment of ventricular synchrony. Quantifying the temporal dispersion in contractility has provided important insights into the load dependency of ventricular dyssynchrony, 40 the linkage between dyssynchrony and impaired contractile function, 41 and the prognostic relevance of dyssynchrony in select groups of patients with QRS duration Ͻ120 ms. 42 These measures have also been used to assess the relationship between dyssynchrony measures and response after resynchronization therapy. Using both the magnitude and timing of regional deformation, Delgado et al 43 demonstrated the importance of both lead positioning and contractile function, as they relate to the most delayed myocardial segment, in predicting response to cardiac resynchronization therapy.…”
Section: Quantification Of Regional Functionmentioning
confidence: 99%
“…One approach is to focus on those parameters more closely associated with clinical outcomes, and in this respect longitudinal deformation currently appears most promising. 42,46,48,50 In addition, few data are available regarding the feasibility and reproducibility of these measures when applied broadly, particularly for the regional measures. Moreover, data are lacking from large community-based cohorts to define normal ranges for these measures and to describe the manner in which they may vary by age and gender and to establish the relationship between these measures and clinical outcomes.…”
Section: Next Steps In the Application Of Deformation Imagingmentioning
confidence: 99%
“…8 -10 The pronounced mechanical dispersion found in our LQTS patients was related to ventricular arrhythmias and is likely to reflect electric dispersion. Heterogeneous ventricular contraction can also be caused by fibrosis in myocardial tissue and has been related to ventricular arrhythmias 22 and death 23 in patients after myocardial infarction.…”
Section: Electric Dysfunction and Mechanical Consequences In Lqtsmentioning
confidence: 99%